D‐Region High‐Latitude Forcing Factors. Issue 1 (30th January 2019) - Macotela, Edith L.; Clilverd, Mark; Manninen, Jyrki; Moffat‐Griffin, Tracy; Newnham, David A.; Raita, Tero; Rodger, Craig J.
Abstract: The subionospheric very low frequency (VLF) radio wave technique provides the possibility of investigating the response of the ionospheric D‐region to a diversity of transient and long‐term physical phenomena originating from above (e.g., energetic particle precipitation) and from below (e.g., atmospheric waves). In this study, we identify the periodicities that appear in VLF measurements and investigate how they may be related to changes in space weather and atmospheric activity. The powerful VLF signal transmitted from NAA (24 kHz) on the east coast of the United States, and received at Sodankylä, Finland, was analyzed. Wavelet transform, wavelet power spectrum, wavelet coherence, and cross‐wavelet spectrum were computed for daily averages of selected ionospheric, space weather, and atmospheric parameters from November 2008 until June 2018. Our results show that the significant VLF periods that appear during solar cycle 24 are the annual oscillation, semiannual oscillation, 121‐day, 86‐day, 61‐day, and solar rotation oscillations. We found that the annual oscillation corresponds to variability in mesospheric temperature and solar Lyman‐α (Ly‐α) flux and the semiannual oscillation to variability in space weather‐related parameters. The solar rotation oscillation observed in the VLF variability is mainly related to the Ly‐α flux variation at solar maximum and to geomagnetic activity variation during the declining phase of the solar cycle. Our results are important since they strengthen our understanding of the Earth's D‐region response to solar and atmospheric forcing. Key Points: D‐region periodic variations are studied using wavelet analysis of 10 years of high‐latitude subionospheric VLF waves Mesospheric temperature is more related to daytime VLF annual oscillations but nighttime is more related to solar Lyman‐α flux The 27‐day solar rotation period dominates solar declining phase and all periods shorter than annual are transitory